2021
DOI: 10.24191/jeeir.v9i3.14596
|View full text |Cite
|
Sign up to set email alerts
|

The effect of intellectual capital and shariah supervisory boards on social performance of Islamic banks

Abstract: This study examined Islamic banks' social performance by considering Intellectual Capital (IC) and Shariah Supervisory Boards (SSB) as antecedents. More specifically, it examined the antecedents that can exert the role of IC and governance mechanism of SSB in enhancing Islamic banks’ social performance. Therefore, this study empirically analyzed the effect of IC and SSB on social performance in Indonesian Islamic banks with a sample of 14 Islamic banks throughout the period 2008-2019. To test the research hypo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…This is done by Islamic banking because Islamic banking realizes that the knowledge possessed by the workforce is very valuable. (Nurdin & Suyudi, 2019) Different research results were conducted by Jetmiko (2018), Gunawan et al, (2019), andPratama et al (2021) found that intellectual capital did not affect banking did not affect. Meanwhile, research conducted by Aisyah et al, (2021) and Rahma & Atiqah (2021) found negative results between intellectual capital and maqashid sharia performance.…”
Section: The Development Of Islamic Commercialmentioning
confidence: 97%
See 1 more Smart Citation
“…This is done by Islamic banking because Islamic banking realizes that the knowledge possessed by the workforce is very valuable. (Nurdin & Suyudi, 2019) Different research results were conducted by Jetmiko (2018), Gunawan et al, (2019), andPratama et al (2021) found that intellectual capital did not affect banking did not affect. Meanwhile, research conducted by Aisyah et al, (2021) and Rahma & Atiqah (2021) found negative results between intellectual capital and maqashid sharia performance.…”
Section: The Development Of Islamic Commercialmentioning
confidence: 97%
“…In creating value and companies that grow sustainably, Intellectual Capital plays an important role (Pratama et al, 2021). Companies that use it must gain a competitive advantage in the market to create value and achieve peak performance in the future (Pratama et al, 2019).…”
Section: The Influence Of Intellectual Capital On the Maqashid Sharia...mentioning
confidence: 99%
“…Several previous studies have explained that a company's competitive advantage can be associated with corporate social performance (Greening & Turban, 2000;Gregory et al, 2016). From an Islamic banking perspective, previous research (Fatah et al, 2022;Nawaz & Haniffa, 2017;Pratama et al, 2020Pratama et al, , 2021Pratama et al, , 2022Setianto & Sukmana, 2016) has shown that IC has a positive impact on Islamic banking performance. Based on the description above, the hypothesis proposed in this study is as follows: H1: Intellectual capital has a positive effect on the Social Performance of Islamic Banks…”
Section: Literature Review and Hypothesis Development The Effect Of I...mentioning
confidence: 98%
“…As a result, the SSB is concerned with how the IB performs its social functions. The meeting frequency, which indicates the members' monitoring actions, is one SSB element that may be directly related to the company's performance (Pratama et al 2021). Based on the above description, the following hypothesis is offered in this study:…”
Section: Intellectual Capital and Islamic Banks Social Performancementioning
confidence: 99%
“…As a result, the SSB focuses on how the IB carries out its social functions. One feature of the SSB that may be directly tied to the company's performance is the meeting frequency, which represents the members' monitoring actions (Pratama et al 2021). The second factor is gender diversity, which would have a favorable influence on performance if women offered extra oversight to the Board (Adams & Ferreira 2009;Gul et al 2011).…”
Section: Introductionmentioning
confidence: 99%